Effect of Inquiry Model on Mathematical Critical Thinking Ability of Primary School Students - Pratiwi, H S; Prabawanto, S (International Conference on Elementary Education, 2020)
This study aims to analyze the differences between students' mathematical critical thinking under the model of inquiry learning model and those under the expository model. The experiment was conducted in an elementary school in Sukabumi, academic year 2018/2019. The sample were 42 of fourth graders, which were divided into two groups, namely experiment group and control group. Each group consist of 21 students. This type of research was a quasi-experimental with pretest-posttest control group design. The data were collected by using mathematical critical thinking tests. The data analysis technique used was the difference of means of results of tests from both the experimental group and the control group at the significance level α = 0.05. The results show that there are differences between students' mathematical critical thinking under the inquiry model with those under the expository model. Further analysis show that the students’ mathematical critical thinking under the inquiry model is better than those under expository model